Carrier-free curcumin nanoassemblies for enhancing therapy effects in inflammation related disease. (October 2022) - Zhang, Liangjun; Xia, Haihan; Du, Song; Zhao, Nan; Zhang, Xiaoxun; Pan, Qiong; Xu, Senlin; He, Zhicheng; Yi, Zeng; Chai, Jin
Graphical abstract: Highlights: This study provided a strategy for synthesizing carrier-free curcumin, quercetin and resveratrol-based nanomedicines with one-pot method, that is overcoming the dilemma of complexity carrier synthesis and drug low loading rate. Curcumin nanomedicines not only decreased the cytotoxicity of curcumin but also preserved its anti-inflammatory activity. In the acute and chronic inflammation models, including sepsis, IBD, and liver fibrosis, nanomedicines showed a better therapeutic effect than free curcumin. Abstract: Hyperinflammation can lead to tissue injury, organ failure, and even fatalities by overproducing proinflammatory cytokines. The long-term safety and outstanding anti-inflammatory ability of natural products have attracted much attention, but the low solubility and bioavailability limit their application. In this study, PGDE was conjugated with aromatic hydroxy groups of curcumin, resveratrol, and quercetin to prepare polyphenolic nano-assemblies. The nano-assemblies showed a comparable capacity for scavenging DPPH and ABTS free radicals with curcumin. The modification not only decreased the cytotoxicity of curcumin but also the anti-inflammation activity was preserved successfully. In vivo tests, NCAs were preferentially located at the inflammatory sites and performed effective therapeutic effects on acute and chronic inflammation models including sepsis, IBD, and liver fibrosis models. The anti-inflammatory activities were primarily realized by suppressing the overproduction of TNF-α, IL-6 and IL-β cytokines, and down-regulating the ROS-related NOX-1 and NOX-4. Additionally, NCAs inhibited the activation of the TGF-α/Smad pathway and decreased the production of α-SMA to alleviate collagen deposition in fibrosis mice. This study described a simple method for preparing nano-assemblies of insoluble polyphenols via the carrier-free self-assembly method, which improved the therapeutic effect on inflammatory diseases and broadened the application field of insoluble natural active polyphenols.